Perbandingan Kemampuan Pemahaman Matematis Siswa melalui Auditory Intellectualy Repetition dan Student Teams Achievement Division - Ridia, Noni Siti; Afriansyah, Ekasatya Aldila (Department of Mathematics Education Program IPI Garut, 2019)
Kondisi pembelajaran saat ini cenderung kurang melibatkan siswa dalam proses pembelajaran meskipun siswa tampak mengikuti pembelajaran matematika dengan baik serta kemampuan pemahaman matematis siswa masih tergolong rendah. Strategi yang dapat melibatkan siswa dan meningkatkan kemampuan pemahaman dalam pembelajaran diantaranya model pembelajaran Auditory Intellectually Repetition dan Student Teams Achievement Division. Penelitian ini menggunakan metode penelitian kuasi eksperimen dengan desain Nonequivalent control group design. Sampel penelitian yang diambil sebanyak 59 orang dari dua kelas, yaitu kelas VII-D menggunakan model pembelajaran Auditory Intellectually Repetition sebanyak 29 orang dan kelas VII-E menggunakan model pembelajaran Student Teams Achievement Division sebanyak 30 orang. Instrumen yang digunakan yaitu tes kemampuan pemahaman matematis dan angket skala sikap. Hasil penelitian menunjukkan bahwa kemampuan pemahaman matematis siswa yang mendapatkan model pembelajaran Auditory Intellectually Repetition tidak lebih baik daripada siswa yang mendapatkan model pembelajaran kooperatif tipe Student Teams Achievement Division. The current learning conditions tend to involve fewer students in the learning process even though students seem to follow mathematics learning well and the students' mathematical understanding ability is still relatively low. Strategies that can involve students and improve the ability to understand in learning include the Auditory Intellectually Repetition learning model and Student Teams Achievement Division. This research method uses quasi-experimental research with Nonequivalent control group design. The research sample was taken as many as 59 people from two classes, namely class VII-D using the Auditory Intelligence Repetition learning model as many as 29 people and class VII-E using 30 students Teams Achievement Division learning model. The instrument used is a mathematical understanding ability test and attitude scale questionnaire. The results showed that the students' mathematical comprehension ability who received the Auditory Intellectually Repetition learning model was no better than the students who received the cooperative learning model of Student Teams Achievement Division.